STUDI KERAGAMAN GENETIK Diospyros rumphii Bakh DI SULAWESI UTARA BERDASARKAN PENANDA ISOENZIM - Julianus Kinho; Mohammad Na'iem; Sapto Indrioko (Jurnal Pemuliaan Tanaman Hutan, 2016)
Diospyros rumphii Bakh. is one of tropical commerciall wood species grouped in ebony. Ebony is the name of some species of commercial timber from genus of Diospyros (Ebenaceae). Seven species of them are commercial wood, which in the trade is known as ebony namely; D.celebica, D.rumphii, D.pilosanthera, D.lolin, D.ebenum, D.ferrea and D.macrophylla. Two of seven species ebony have the highest economic values namely; D.celebica and D.rumphii. Nowadays, the population D. rumphii in the nature are decreases due to over harvesting in the past. This study aims to determine genetic diversity of D. rumphii within populations, between populations and its relationship. The samples of D. rumphii in this study from four populations in North Sulawesi i.e Bitung, Talise, Talaud and Bolaang Mongondow. Genetic diversity was detected by isoenzym markers with seven enzyme i.e Glutamate oxaloacetate transmirase (GOT), Shikimate dehydrogenase (SHD), Esterase (EST), Acid phoshatase (ACP), Diaphorase (DIA), 6-Phosphogluconate dehydrogenase (6PG) and Glutamate dehydrogenase (GDH). The results showed that there are three enzym was detected polymorphisme i.e EST, GOT and GDH. Genetic diversity generated by three enzyme systems who are controlled by 5 loci and 15 alleles. The average percentage of polymorphic loci was100%. The number of total genetic diversity is 0.64,which are distributed within population 0.59 (91.24%) and between population 0.05(8.76%). Cluster analysis using Unweighted Pair Group Method with Aritmatic Means (UPGMA) based on Nei standard genetic distance showed three clusters:Bitung and Bolaang Mongondow, Talise, and Talaud.